Model Media Pembelajaran Sains untuk Anak Berkebutuhan Khusus - Nur Fajrie; Siti Masfuah (Bagimu Negeri, 2018)
This article aims to describe devotion activities to a special school (SLB)’s teachers in Kudus regency about the models of science learning media for children with special needs (ABK). This activity is done by SLB’s teachers in Kudus regency, beginning with need analysis through literature and field study, workshop and mentoring activities, media implementation and product evaluation. The instruments used were interview sheets, observation sheets, questionnaires and test of learning outcomes. Based on the evaluation of practicality aspects, the media was easy to make and easy to use. Based on efficiency aspects, the media was made of safe materials, easy to obtain and affective’s cost. Based on effectiveness, this media was to facilitate teachers to explain the materials to ABK and the learning outcomes increased.Keywords: Science Learning Media, Children With Special Needs